Using pharmacological manipulations to study the role of dopamine in human reward functioning: A review of studies in healthy adults - Webber, Heather E. (Neurosci Biobehav Rev, 2020)
Dopamine (DA) plays a key role in reward processing and is implicated in psychological disorders such as depression, substance use, and schizophrenia. The role of DA in reward processing is an area of highly active research. One approach to this question is drug challenge studies with drugs known to alter DA function. These studies provide good experimental control and can be performed in parallel in laboratory animals and humans. This review aimed to summarize results of studies using pharmacological manipulations of DA in healthy adults. ‘Reward’ is a complex process, so we separated ‘phases’ of reward, including anticipation, evaluation of cost and benefits of upcoming reward, execution of actions to obtain reward, pleasure in response to receiving a reward, and reward learning. Results indicated that i) DAergic drugs have different effects on different phases of reward; ii) the relationship between DA and reward functioning appears unlikely to be linear; iii) our ability to detect the effects of DAergic drugs varies depending on whether subjective, behavioral, imaging measures are used.